Dynamic Matching and Bargaining Games: A General Approach - Lauermann, Stephan (American Economic Review, 2013)
Dynamic matching and bargaining games are models of decentralized markets with trading frictions. A central objective is to investigate how equilibrium outcomes depend on the level of frictions. In particular, does the trading outcome become Walrasian when frictions become small? Existing specifications of such games provide divergent answers. This paper presents a new characterization result for competitive allocations in quasilinear economies. The characterization result is used to investigate what causes these differences and to generalize insights from the analysis of specific matching and bargaining games. (JEL C73, C78, D82, D83)